Bioactivity of Alstonia boonei De Wild leaf alkaloid on the growth and development of Maruca vitrata Fab. - Oigiangbe, O.N.; Tamo, Manuele; Igbinosa, I.B. (2013)
The bioactivity of Alstonia boonei De Wild leaf alkaloid was tested under laboratory bioassay against the legume pod borer, Maruca vitrata Fabricius. The alkaloid was incorporated into standard M. vitrata artificial diet at five doses [0.00 % (Control), 0.02 %, 0.05 %, 0.10 % and 0.20 %], and fed to the newly emerged first instar M. vitrata larvae in plastic wells under laboratory conditions. Significant differences (P < 0.05) were recorded in the larval survival, wet and dry weights of the larvae at ten days after infestation (DAI). Mean larval survival ranged from 34.78 to 65.00 percent in the treatments with the alkaloid compared with 91.67 percent in the control. At 15 DAI, all the survivors in the control had pupated normally compared with the 4.34 to 35.00 percent pupation (with various levels of deformity) in the treatments with the alkaloid. The mean percentage adult emergence was also significantly different in the control (83.33 %) compared with the other treatments (range 0.00 to 10.00 %). These results indicate a high level of bioactivity of A. boonei leaf alkaloid against M. vitrata. It is concluded that the alkaloid has a great potential in the search for bioactive compounds for the management of the insect.